Enhancing Distributed Software Development with Collaborative Technology (International Journal of Engineering and Computer Science, 2013)
Distributed Software Development Has Become Increasingly Common In Recent Years Due To Its Potential For Cost Savings And Access To A Larger Talent Pool. However, It Poses Significant Challenges Related To Coordination, Communication, And Collaboration. Collaborative Technology Can Enhance Distributed Software Development By Enabling Effective Communication And Coordination Among Team Members. This Paper Explores The Concept Of Enhancing Distributed Software Development With Collaborative Technology, Including An Overview Of The Various Collaboration Tools, Such As Version Control Systems, Issue Tracking Systems, And Project Management Tools. The Paper Serves As A Useful Reference For Researchers, Practitioners, And Stakeholders Involved In Distributed Software Development.